2016
DOI: 10.1038/srep34167
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endoplasmic Reticulum Stress, Autophagy and Apoptosis in Advanced Glycation End Products-Induced Glomerular Mesangial Cell Injury

Abstract: Advanced glycation end-products (AGEs)-induced mesangial cell death is one of major causes of glomerulus dysfunction in diabetic nephropathy. Both endoplasmic reticulum (ER) stress and autophagy are adaptive responses in cells under environmental stress and participate in the renal diseases. The role of ER stress and autophagy in AGEs-induced mesangial cell death is still unclear. Here, we investigated the effect and mechanism of AGEs on glomerular mesangial cells. AGEs dose-dependently decreased mesangial cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 53 publications
0
36
0
1
Order By: Relevance
“…60,61 More recently, it has also been implicated in peroxisome biogenesis 62,63 and regulation of the cellular process autophagy. 35,36,55,64,65 These studies suggest a wide range of possible activities by 4-PBA that are highly dependent on the cell type, dosage, and treatment regime. However, as alluded to previously, very few of these studies have been conducted in the context of macrophage polarization by LPS.…”
Section: Discussionmentioning
confidence: 93%
“…60,61 More recently, it has also been implicated in peroxisome biogenesis 62,63 and regulation of the cellular process autophagy. 35,36,55,64,65 These studies suggest a wide range of possible activities by 4-PBA that are highly dependent on the cell type, dosage, and treatment regime. However, as alluded to previously, very few of these studies have been conducted in the context of macrophage polarization by LPS.…”
Section: Discussionmentioning
confidence: 93%
“…Because ER stress plays important roles in osteoblast apoptosis and osteoporosis, (15,25) we hypothesized that intracellular AGEs induced osteoblast apoptosis via ER stress. Therefore, we examined the effect of GA on ER stress signaling in MC3T3-E1 cells.…”
Section: Involvement Of Er Stress With Ga-induced Age Accumulation Wimentioning
confidence: 99%
“…(13) Recent reports have shown that extracellular AGEs induce apoptosis via ER stress in diverse cell types. (14,15) However, little is known regarding the effects of intracellular AGEs on the activation of ER stress in osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Le transforming growth factor b (TGF), une cytokine profibrosante ayant un rôle important dans la physiopathologie de la glomérulosclérose, induit l'autophagie dans les cellules mésangiales réduisant la production de matrice mésangiale en initiant la dégradation de collagène de type I, un effet a priori bénéfique de l'autophagie dans le processus [34]. Le flux autophagique peut également être activé dans les cellules mésangiales en réponse à la production d'AGE, mais les conséquences de ce processus sur le développement de la néphropathie diabétique restent inconnues [35].…”
Section: Autophagie Rénaleunclassified